Indigenous Peoples: From Unrighteousness to the Right to Self-Government (Lex localis - Journal of Local Self-Government, 2010)
In the past, indigenous peoples were exposed to many violations of human rights. They were treated as nations without rights and civilisation. Colonial powers confiscated their land without paying any compensation. Their culture, religion, language, social and judicial systems were annulled or even destroyed. Members of indigenous peoples were victims of ethnocide/genocide and were used as cheap labour force. Today, many live on the edge of human society and deal with different problems (alcohol, drugs, crime). National efforts and trends to abolish the injustice made in the past, and efforts for the improvement of the present situation of members of indigenous peoples have brought fruit because indigenous peoples have reached a certain degree of autonomy in different countries through the right to self-determination and the right to self-government. Declaration on the Rights of Indigenous Peoples was adopted in 2007. It represents an important milestone in resolving many issues associated with indigenous peoples, even though individual countries with many indigenous peoples have not supported it.